A re-visit to the concept of freewill and ideas of causality in Yoruba religion (2016)
The issue of human will has been a subject of much debate in the history of philosophy and within religious circles over the Centuries. This paper examines the subject of freewill and ideas of causality in the indigenous religion of the Yoruba. Ideas of causality feature prominently in the belief Systems of Yoruba religion expressed in the concepts of Ori, Irawo, Ipin, Ogo, Kadara, Akunlegba, Akunleyan and Ayanmo and other similar ideas revolving around determinism. These ideas of causality lead to a hasty conclusion in most cases that freewill does not exist among the Yoruba. Insisting that there is no freewill has serious implications within a practical milieu especially because of individual responsibility for actions. This paper is a departure from the notion that there is no freewill among the Yoruba. This is done by discussing the meaning of freewill with a view to finding a definition suitable in the Yoruba religious contexts which is clearly different from the Western idea of freewill. This paper also discusses how the concept of freewill and issues related to determinism feature in Yoruba beliefs. This paper employs the Compatibilism theory, the current name for William James’ “soft" determinism, which is the logically contradictory notion that free will is compatible with determinism. This is done with a view to drawing the conclusion that freewill exists among the Yoruba in spite of the established ideas of causality.